PENYULUHAN PRE-OPERATIF DAN LABIOPALATOSCHIZIS - Nanda Nur Fauziah; Wirawan Anggorotomo; Moch. Alia Febriansyah; Lintang Dhyta; Noviana Pratiwi; Ainayya Dinari; Nadya Salsabila (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2024)
Pre-operative management is one of the stages that must be carried out by an anesthesiologist, this is the initial stage that is carried out which determines whether the patient will be operated on, whether he can carry out the operation or not. Labiopalatoschizis or cleft lip is a congenital condition characterized by a gap in the lip accompanied or without a gap in the oral cavity (pallatum). Knowledge of pre-operative procedures is still often ignored by some patients, especially instructions for fasting and knowledge of labiopalaoschizis is still lacking in the community, especially regarding causes, complications, etc. The purpose of this education is to provide more knowledge about the importance of following instructions before starting surgery, and to provide a general explanation regarding labiopalatoschizis. The implementation method used is counseling for parents/guardians of children who will have surgery, followed by a question and answer session. The results found that 70% of the public did not understand the importance of pre-operative measures and regarding labiopalatoschizis.